PRAKTIK KERJA LAPANGAN SEBAGAI MATA PELAJARAN DI SEKOLAH MENENGAH KEJURUAN - Rahmatullah, Noris; Pratiwi Dharma, Agricynthia; Aramitha Safitri, Dinda (Jurnal Pembelajaran Inovatif, 2025)
This study aims to see how the implementation of On Job Training (PKL) as a school subject in Vocational High School (SMK). This study uses a quantitative approach with a descriptive research type. The data sources for this study were 853 SMK educational units spread across 31 provinces. The results of the study were 84.53% of the PKL implementation time in accordance with the guidelines, 99.50% of the PKL implementation was offline. During the implementation of PKL, 99.18% supervising teachers provided assistance either online, offline, or a combination of online and offline. For the PKL assessment component, schools used PKL journals, reports, presentations, and competency tests as PKL assessment components. The conclusion of this study is that schools are able to implement PKL as a subject in accordance with the guidelines by the Ministry of Education, Culture, Research, and Technology.